(untitled) - Cooper, Jason; 1942- (Vero Beach, Fla., 1991)
Describes the construction, purpose, and parts of dams throughout the world.
Translation of: Dams.
Includes index.
Keywords: Dams; Juvenile literature; Dams; Spanish language materials